Complete telomere-to-telomere genomes uncover virulence evolution conferred by chromosome fusion in oomycete plant pathogens - Zhang, Zhichao; Zhang, Xiaoyi; Tian, Yuan; Wang, Liyuan; Cao, Jingting; Feng, Hui; Li, Kainan; Wang, Yan; Dong, Suomeng; Ye, Wenwu; Wang, Yuanchao (Nature communications, 2024)
Variations in chromosome number are occasionally observed among oomycetes, a group that includes many plant pathogens, but the emergence of such variations and their effects on genome and virulence evolution remain ambiguous. We generated complete telomere-to-telomere genome assemblies for Phytophthora sojae , Globisporangium ultimum , Pythium oligandrum , and G. spinosum . Reconstructing the karyotype of the most recent common ancestor in Peronosporales revealed that frequent chromosome fusion and fission drove changes in chromosome number. Centromeres enriched with Copia -like transposons may contribute to chromosome fusion and fission events. Chromosome fusion facilitated the emergence of pathogenicity genes and their adaptive evolution. Effectors tended to duplicate in the sub-telomere regions of fused chromosomes, which exhibited evolutionary features distinct to the non-fused chromosomes. By integrating ancestral genomic dynamics and structural predictions, we have identified secreted Ankyrin repeat-containing proteins (ANKs) as a novel class of effectors in P. sojae . Phylogenetic analysis and experiments further revealed that ANK is a specifically expanded effector family in oomycetes. These results revealed chromosome dynamics in oomycete plant pathogens, and provided novel insights into karyotype and effector evolution. Frequent chromosome fusion and fission in oomycetes drive changes in chromosome number. Here, Zhang et al show that these dynamics facilitate the adaptive evolution of genes related to pathogenicity.